Coaxial-to-Microstrip Transition for 5G Millimeter Wave Communication Band - Wang, Heesu; Park, Ikmo (GSMM 2021 - 2021 Global Symposium on Millimeter-Waves and Terahertz, Proceedings, 2021)
This paper presents a coaxial-to-microstrip transition with improved transmission characteristics for use in 5G millimeter wave communication band. When a coaxial cable and a microstrip line are connected, a discontinuous portion exists at the connection, and the reflection, transmission, and radiation of the incident electromagnetic waves occur due to the discontinuity. To prevent degradation of the transition characteristics due to the discontinuity, metal legs in the coaxial cable are introduced. The proposed coaxial-to-microstrip transition has a higher transmission coefficient than conventional coaxial-to-microstrip transitions.
Keywords: Microstrip transitions; Millimeter-wave communication; Transmission characteristics; Transmission coefficients; 5G communication; coaxial-to-microstrip transition; improved transmission; metal leg; millimeter-wave